Tourism : principles, practices, philosophies - Goeldner, Charles R.; Ritchie, J. R. Brent (Hoboken, New Jersey : Wiley, 2006)
Tourism: Principles, Practices, Philosophies explores major concepts in tourism, what makes tourism possible, and how tourism can become an important factor in the wealth of any nation. It is written in global terms, making it appropriate not only in the US but also for our subsidiary markets.
1. Tourism overview -- Tourism in perspective -- Tourism through the ages -- Career opportunities -- 2. How tourism is organized -- World, national, regional, and other organizations -- Passenger transportation -- Hospitality and related services -- Organizations in the distribution process -- Attractions, entertainment, recreation, and other tourist draws -- 3. Understanding travel behavior -- Motivation for pleasure travel -- Cultural and international tourism for life's enrichment -- Sociology of tourism -- 4. Tourism supply, demand, policy, planning, and development -- Tourism components and supply -- Measuring and forecasting demand -- Tourism's economic impact -- Tourism policy: structure, content, and process -- Tourism planning, development, and social considerations -- Tourism and the environment -- 5. Essential of tourism research and marketing -- Travel and tourism research -- Tourism marketing -- 6. Tourism prospects -- Tourism's future.
Includes bibliographical references and index.
Keywords: TOURISM